Formulation and Evaluation of Lisinopril Dihydrate Transdermal Proniosomal Gels - Shamsheer Ahmad S, Sabareesh M, Patan Rafi Khan, Sai krishna P, Sudheer B. (Journal of Applied Pharmaceutical Science)
In the present study transdermal Lisinopril proniosomal gels was formulated by using Lecithin, Cholesterol as encapsulating agents, Surfactant, Span and permeation enhancers. The study methodology encompasses compatibility studies using FTIR spectra, evaluation of proniosomal gels for pH determination, Viscosity, Vesicle size analysis, rate of spontaneity, encapsulation efficiency, in vitro skin permeation studies and stability studies. The preliminary compatibility studies conducted revealed that there no interaction between Lisinopril and excipients which was as evident from FTIR spectral studies. The physical characterization of proniosomal gels was found to be within the acceptable limits. It was observed that the gel formulations showed good spreadability and viscosity. Determination of vesicle size was found to be 20.10-26.23µm. The proniosomes showed spherical and homogenous structure in optical microscopy. All formulations showed zero order drug release by diffusion mechanism. The stability studies showed that proniosomal gels were stable at 4 to 80C and 25±20C. The above results indicated that the proniosomal gels of could be formulated for controlled release of Lisinopril. The proniosomal gels are suitable for Lisinopril once a day controlled release formulation.
Keywords: Lisinopril, Pronoisomes, Lecithin, Cholesterol, Transdermal gel.